The Impact of Organizational Design on the Effectiveness of Project Management: A Case Study from the UAE Public Sector - Ibrahim, Ahmed M. (2015)
The research on project management effectiveness has been extensive and controversial infused by the pragmatic need for project management (PM) to achieve tangible and predictable results in practice. The notion that organizations of all sorts can realize their goals by using project management in their businesses, increase the challenge for project-based organizations (PBO) to succeed in project management using project management. This study provides an example on how to investigate the status of project management effectiveness in PBOs in order to enhance their performance. To approach the first part of the problem, the five processes of project management were identified from prevailing PM standards, being PMBOK and OPM3, to determine the subject of effectiveness – which is the effective succession of projects through the phases of initiation to closing. Then a theoretical process maturity model (PM²) was used to articulate the descriptive characteristics of PM effectiveness for each process. The finding was that comparing the process maturity level (PML) to actual project performance can reveal the status of effectiveness for each of the processes, which opens the door to questioning the organizational factors affecting such status. In the second part of the problem, the complexities of the organizational phenomenon was reduced to a single research-based definition i.e. organizational design, to allow for the pluralization of the structural and social characteristics accentuating the organization’s reality. Five organizational structure dimensions and their substantiated attitudes and behaviours were identified to study, through them, the impact of organizational design on project management effectiveness in the organization selected for study (ABC). Data was collected from eight members of the organization using a detailed case-study methodology. The ’expert interview’ questions were aligned with, and backed by, the theoretical findings of the literature review and organized into five groups, firstly, to identify the organization’s state of effectiveness and, secondly, to identify the structural and behavioural characterises associated with the current PM effectiveness. The study culminate by concluding that organizational design and PM effectiveness are correlated based on the findings confirming that as much as the organizational factors control people’s behaviour, they also make the people develop reversed behaviours that either impair or enhance the status of effectiveness, in return.